Career Counseling Using a Trait and Factor Approach to Help Students in Making Career Decisions - Avira Heriani; Firman Firman; Mohd Nazri Abdul Rahman; Netrawati Netrawati (Universitas Muhammadiyah Enrekang, 2024)
This research explores group counseling with a trait and factor approach in supporting students in making career decisions. This approach emphasizes the identification of personal characteristics and factors related to career choice, providing a solid foundation for the decision-making process. The literature study method was used to collect data. The research results show that the trait and factor approach is able to provide a deeper understanding of students' strengths, interests and values, which positively influences their ability to make informational career decisions based on self-reflection.